2007
DOI: 10.7589/0090-3558-43.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Rabies in Bats from Alabama

Abstract: ABSTRACT:Data on rabies virus infection in bats that were submitted to the Alabama Department of Public Health from 1995-2005 were analyzed. Demographic factors, such as species and sex, and temporal aspects, such as yearly and monthly trends, were investigated. Thirteen species of bats were submitted, and of those, individuals from seven species were rabid; prevalence was highest in Lasiurus borealis and Pipistrellus subflavus and lowest in Eptesicus fuscus and Nycticeius humeralis. There was no difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
6
2
Order By: Relevance
“…In disagreement with Hester et al 12 , who reported that rabies prevalence in solitary species submitted for rabies diagnosis in the USA and Canada is consistently greater than in colonial species, even though the largest number of rabies cases were determined in the colonial bat Eptesicus fuscus, in this work, only six of the rabiespositive bats were from solitary species. In our sample, prevalence seems be more directly related to species habit in urban areas, which use cramped locals as shelter with intense body contact among individuals, than solitary or colonial species.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In disagreement with Hester et al 12 , who reported that rabies prevalence in solitary species submitted for rabies diagnosis in the USA and Canada is consistently greater than in colonial species, even though the largest number of rabies cases were determined in the colonial bat Eptesicus fuscus, in this work, only six of the rabiespositive bats were from solitary species. In our sample, prevalence seems be more directly related to species habit in urban areas, which use cramped locals as shelter with intense body contact among individuals, than solitary or colonial species.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this difference regarding sex was not observed by others authors 12,15,16 . In some species, females live in maternity colonies segregated from the males.…”
Section: Conflict Of Interest Referencescontrasting
confidence: 42%
See 1 more Smart Citation
“…This is attributed to their territorial behavior and increased aggression during the mating season (60). In contrast, in North American insectivorous bat species, rabies was detected evenly in males and females (11,20,24) or the occurrence of infection among females was greater than among males (7,8). The latter was also true for EBLV-1-infected insectivorous bats in The Netherlands (63).…”
Section: Discussionmentioning
confidence: 99%
“…However, tricolored bats were more frequently submitted in Tennessee compared with neighbor states Alabama and South Carolina (Parker et al 1999;Hester et al 2007). Bat species was a key predictor of rabid bats and the highest proportion was observed among lasiurine bats.…”
Section: Species Composition Of Submissions Inmentioning
confidence: 94%